Toward a new era of digital economy - Chuncong LU (Dianxin kexue)
The digital economy is to supply digital elements with rich elements,improve the efficiency of factor allocation by network,improve output efficiency intelligently,and promote economic development quality change,efficiency change,and power change.Firstly,the importance of grasping the new opportunities for the development of the digital economy was explained.Then the rapid growth of the digital economy and the significant situation of the digital economy driving employment was introduced.Finally,key points of promoting the development of the digital economy were focused on.The next step is to accelerate the application of industrial internet construction,promote the digital transformation of enterprises,improve the policy environment,strengthen the protection of factors,and further promote the prosperity and development of the digital economy.